Power model in power analysis attack - Peng LUO; Deng-guo FENG; Yong-bin ZHOU (Tongxin xuebao)
A mapping relation model should be established between data value and power value which is collected from device under attack when the power analysis attack accuse.The sensitive information can be fund through the power trace analysis using this type of relation.Hamming distance model and hamming weight model were described based on device’s physical characteristics.Furthermore,the correctness of hamming weight model was proved not only by Formula Derivation,but also by experiment under power consumption collection platform based on MCU.The experimental results show that hamming weight model is a valid and practicable model in power analysis attack.